Analisis Pelaksanaan Pengelolaan Keuangan Desa: Studi Kasus Desa Kemuning Lor Kecamatan Arjasa Kabupaten Jember - Linda Aviva; Dessy Putri Andini (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study aims to determine the implementation of village finances based on Permendagri No. 20 of 2018 concerning Village Financial Management. This study used a descriptive qualitative method, which carried out direct observations in the field, namely Kemuning Lor Village, Arjasa District, Jember Regency. Research instruments are used through documentation, observation, interviews and literature study by collecting every document needed in this study, then the documents are analyzed using the Creswell model, by recording the required data which is adjusted to Permendagri No. 20 2018. The documents needed in this study are the 2019 Kemuning Village APBDes. Data analysis techniques use triagulation in the process of searching and systematically compiling data obtained from interviews, field notes, so as to provide conclusions about the implementation of village financial management in accordance with the Regulation Domestic Affairs No. 20. Year 2018 concerning Village Financial Management.